2016
DOI: 10.4314/ejhs.v26i4.3
|View full text |Cite
|
Sign up to set email alerts
|

The effect of job demand-control-social support model on nurses’ job satisfaction in specialized teaching hospitals, Ethiopia

Abstract: BACKGROUND: The job demand-control-social support model has been widely studied in western countries but has not been theoretically addressed on health workers of sub-Saharan African countries. Therefore, this study investigates the relationship between Job Demand-Control-Support Model and job satisfaction in specialized teaching hospitals in Ethiopia. METHOD: A cross-sectional survey was conducted from September 2014 to May 2015 in three public specialized teaching hospitals in Ethiopia. Among 1371 nurses, 36… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 35 publications
0
31
0
1
Order By: Relevance
“…The final structural equation model was accepted based on a set of fit measures, and analyses confirmed the hypothesized pathways of each variable guided by a modification process on empirical and theoretical grounds. Previous studies examined the moderating or motivating role played by work environments and characteristics or personality-related emotional display factors to affect burnout and job satisfaction among doctors or nurses, [ 24 , 31 35 ] but studies on pharmacists are rare. Our study provides complementary findings by investigating hospital pharmacists’ awareness of burnout and job satisfaction and investigating the distinction between pharmacists and other health workers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The final structural equation model was accepted based on a set of fit measures, and analyses confirmed the hypothesized pathways of each variable guided by a modification process on empirical and theoretical grounds. Previous studies examined the moderating or motivating role played by work environments and characteristics or personality-related emotional display factors to affect burnout and job satisfaction among doctors or nurses, [ 24 , 31 35 ] but studies on pharmacists are rare. Our study provides complementary findings by investigating hospital pharmacists’ awareness of burnout and job satisfaction and investigating the distinction between pharmacists and other health workers.…”
Section: Discussionmentioning
confidence: 99%
“…According to the job strain model, workers who are exposed to high levels of demands, but have low levels of job control are more likely to exhibit increased levels of depression, fatigue, cardiovascular disease, and mortality. [ 18 ] Job demand has a significant but negative relationship with job satisfaction, [ 35 ] but job control has the most consistent impact with direct effects on job satisfaction, psychological distress, and depression. [ 33 ] In this study, the impacts of job control and workload on burnout and job satisfaction were similar.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that the JDC model ‘job demand’ had a significant but negative relationship with job satisfaction, social support had a significant and positive relationship with job satisfaction, and high demands and lower social support affected the intention to leave ( 29 , 30 ). Also in the present study this relationship, often referred to as iso-strain, was established.…”
Section: Discussionmentioning
confidence: 96%
“…High work demands, low control over the work process and lack of social support significantly influence satisfaction ( 21 , 29 - 30 ) . A study on the interaction of the psychosocial factors with the Burnout dimensions showed that the psychological demand was the one most related to emotional exhaustion, while control over the work process was more associated with depersonalization and personal fulfillment ( 31 ) .…”
Section: Discussionmentioning
confidence: 99%